The Impact of COVID-19 on Subjective Well-Being: Evidence from Singapore - Terence Chai Cheng; Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2020)
We provide novel evidence on how the COVID-19 global health and economic crisis is affecting overall life satisfaction and domain-specific satisfaction using data from a monthly longitudinal survey of middle-aged and older Singaporeans. Using a difference-in-differences framework, we document large declines in overall life satisfaction and domain-specific satisfaction during the COVID-19 outbreak, except satisfaction with health. These declines coincide with the introduction of a nationwide lockdown, with life satisfaction remaining below its pre-pandemic levels even after the lockdown is lifted. We also find that individuals who report a drop in household income during the COVID-19 outbreak experience a decline in overall life satisfaction almost twice as large as those who do not report any income loss.
Keywords: E2; I12; I31; 330; COVID-19; pandemic; life satisfaction; subjective well-being; individual-level monthly panel data; difference-in-differences